Strategi Pengembangan Ekowisata di Objek Ekowisata Danau Kaenka, Kecamatan Mollo Utara, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Maharani Putri Mimy; Mamie E. Pellondo'u; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
In the Mutis Timau protected forest area there are various natural and cultural attractions, one of which is Lake Kaenka which is a developed ecotourism spot. Research on the area was conducted to determine the potential that exists and the development strategy that will be used in the area so that it can determine the impact of ecotourism development on the economic conditions of the community in Fatukoto Village. This research took place for two months, namely October - December 2022 in Fatukoto Village, North Mollo District, South Central Timor Regency, East Nusa Tenggara Province. Respondents in this study amounted to 106 people consisting of 6 managers and 10 people from the community who were obtained using the Snowball Sampling method, while 90 visitors were obtained using the accidental sampling method or incidental technique with the linear time function (LTF) sampling formula and then analyzed using the ADO-ODTWA analysis method, SWOT analysis, and Interactive data analysis method. The results showed that (1) the total potential feasibility value of the 7 assessment variables was 65.61% so that Lake Kaenka Ecotourism was not yet feasible and had to increase the existing potential. (2) The development strategy obtained is by optimizing management, seeking equitable transportation, forming tourism awareness community groups and developing tourist attractions. (3) Lake Kaenka Ecotourism can increase the income of the surrounding community even though it is not much.